An experimental study on production opportunities of biocomposite by using fungal mycelium - Sağlam, Sebahat Sevde; Acun Özgünler, Seden (Journal of Design for Resilience in Architecture & Planning, 2022)
Due to the adaptability, durability, and affordability of synthetic polymers, their usage has been increasing in the global industry. These petroleum-based polymers remain intact in nature for many years after they expire and cannot be included in the natural recycling network in any way. Producing polymers using fossil resources increasingly day by day threatens existing resources and affects the circular economy negatively. Considering the various negative effects of polymers on the environment, biopolymers could be seen as a strong alternative; which is a polymer group formed by living organisms such as plants, animals, and microorganisms. Ecological, low-emission, and recyclable biopolymers open up new and a broad range of topics in the field. Composite materials created with these biopolymer materials that act as natural adhesives; have different developing areas of applications such as packaging industry, textile, furniture, and industrial design sectors, architectural designs, and structural insulation materials. Fungal mycelium, a biopolymer, consists of fibrous filaments called hyphae, which can be defined as elongated cells, mainly composed of chitin, glucan, and proteins. The ability of fungal mycelium to digest and grow through organic matter makes it possible to produce biocomposites from mycelium. Mycelium-based composites are mixed with fungal mycelium, forming an interpenetrating three-dimensional filamentous network that binds the raw material to the material, and after completing the growth period, the mycelium growth is stopped by heat, thus offering an alternating fabrication paradigm based on the growth of materials.  In this study, firstly, it was tried to find the most efficient ratio among different mixing ratios by using the mycelium of the genus Pleurotus Ostreatus and the same raw materials. Afterward, it was aimed to investigate the mechanical and physical properties through experimental studies, especially the production process, of mycelium-based composites formed by mixing different raw materials in determining proportions.
Keywords: Building construction; mycelium material; sustainable building mateirals; mycelium composite; biopolymers; NA1-9428; biopolymer; sustainable materials; Architecture; mycelium; bio-composite building material; TH1-9745; bio-composite